MENGUNJUNGI TEMPAT SUCI; RAGAM MOTIVASI WISATA RELIGIOUS - Fawaid, Ah. (KARSA Journal of Social and Islamic Culture, 2012)
The journey to the sacred place is a fairly old tradition. In the history of ancient civilization, the sacred place became a magnet for religious believers to do the pilgrimage and magical rituals.The sacred place has become a tourist object from generation to generation. To visit the sacred place is not always identical with rural communities, communities that often are identified as followers of khurafat. Visiting the sacred place is also a city-educated public interest.Like the form of tourism in general, visiting the sacred place may  be just pure entertainment, education, or indeed release a spiritual thirst for community.